Preliminary design of bio-inspired earth-burrowing robot - Tan, Annabelle Mei Hwa (Nanyang Technological University, 2024)
This project aims to improve the present burrowing technologies by utilizing the strategies of burrowing bioerosion from smart organisms found in the marine and freshwater environments of Southeast Asia countries such as Myanmar and Philippines. In this report, inspiration was taken from a freshwater burrowing bivalve found in the silicate rock in Myanmar, also known as Lignopholas fluminalis. This organism mainly utilizes chemical etching and mechanical abrasion as its burrowing strategy in soil and rock. Dynamic friction tests with crushing and embedding on rock particles were performed to further understand the burrowing strategies and to preliminarily design a bio-inspired earth-burrowing robot. Strain gauges, data loggers, tachometer, and acoustic emission (AE) sensors were used to record the results. It was concluded that the highest burrowing efficiency is associated with the combined actions of chemical etching followed by mechanical abrasion under the same load. These preliminary tests then allow for further extensive studies to be conducted before preliminarily designing the bio-inspired earth-burrowing robot.